2011
DOI: 10.19030/iber.v7i8.3280
|View full text |Cite
|
Sign up to set email alerts
|

The Fallacy Of Assuming Equality: Evidence Showing Vastly Different Weighting Of The Global Reporting Initiatives Key Items

Abstract: The press represents the media as a key stakeholder group that is largely ignored by the strategic management branch of stakeholder theory. This study analyses over 2000 articles of the local, regional and national coverage of environmental reporting items to measure press coverage priorities as the weighting mechanism for importance of various environmental issues. The results show a dramatically diverse coverage of the 35 items of the Global Reporting Initiative (GRI). This paper thus provides stakeholder ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Prior CSR reporting studies in Indonesia suggest that these guidelines are appropriate to be used in an Indonesian context (see for example Suhardjanto, Tower and Brown, 2008a;Suhardjanto, Tower and Brown, 2008b). Research has indicated that as there are no clearly detailed CSR guidelines from the Indonesian government or from the Indonesian Institute of Accountants (IAI), that a number of Indonesian companies adopt the GRI guidelines (Lako, 2011;Jalal, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Prior CSR reporting studies in Indonesia suggest that these guidelines are appropriate to be used in an Indonesian context (see for example Suhardjanto, Tower and Brown, 2008a;Suhardjanto, Tower and Brown, 2008b). Research has indicated that as there are no clearly detailed CSR guidelines from the Indonesian government or from the Indonesian Institute of Accountants (IAI), that a number of Indonesian companies adopt the GRI guidelines (Lako, 2011;Jalal, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of environmental disclosure in this study is using the Indonesian environmental disclosure index (IER) developed by [19]. This study analyzes the overall press coverage of Indonesia adopting 35 GRI items, these GRI items are financially or non-financially oriented and the conformity of the assumptions of the same weight inherent in the GRI list.…”
Section: Environmental Disclosurementioning
confidence: 99%
“…Research conducted by [19] analyzed more than 2000 local, regional and national coverage articles from environmental reporting items to measure press coverage priorities as a weighting mechanism for the benefit of various environmental issues. The results show a very diverse range of 35 Global Reporting Initiative (GRI) items.…”
Section: Environmental Disclosurementioning
confidence: 99%
See 2 more Smart Citations